Pengaruh Persepsi Harga, Kepuasan Pelanggan, Dan Kualitas Produk Terhadap Keputusan Pembelian Ulang Di Kopi Studio 24 (Studi Kasus Pada Generasi Z Di Kota Malang) - Fazzira, Amanda Dilla; Priyono, Achmad Agus; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of price perception, customer satisfaction, and product quality on repurchase decisions at Kopi Studio 24 among Generation Z in Malang City. The background of the study is based on the tight competition of the coffee shop industry in Malang, changes in lifestyle, and the importance of customer loyalty. Data were collected through questionnaires to Kopi Studio 24 customers. The findings are expected to be useful for the development of marketing strategies and coffee shop business management. Keywords : Price perception, customer satisfaction, product quality, repurchase, Kopi Studio 24.